Shape your destiny - "Pai, Wamanrao" (Mumbai, 2011)
This book is a specific purpose of mind. The book tells about common man's attitude towards life is fatalistic and negative.This books preaches how to create a strong destiny and helps in achieving success in life.
Keywords: Philosophy of life